2018
DOI: 10.1111/pace.13584
|View full text |Cite
|
Sign up to set email alerts
|

An indissoluble knot: An unexpected troubleshooting during Micra implantation

Abstract: Micra is a transcatheter leadless pacing system delivered percutaneously through femoral vein access into the right ventricle. We are going to describe an initially standard procedure, with an unexpected troubleshooting at the end: the impossibility to release the device and retract the delivery due to a knot in the tether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Moreover, clot formation inside the delivery system has recently been reported in association with a case of indissoluble knot formation. Adequate heparinized saline flow rate was recommended by the authors . In our case, high flow rate of heparinized saline did not prevent knot and clot formation.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, clot formation inside the delivery system has recently been reported in association with a case of indissoluble knot formation. Adequate heparinized saline flow rate was recommended by the authors . In our case, high flow rate of heparinized saline did not prevent knot and clot formation.…”
Section: Discussionmentioning
confidence: 60%
“…Albeit its low incidence, LPM clot formation on the tip of the device or inside the delivery system has been described in the literature. 21 , 22 Device release and delivery system retraction can be interrupted if a clot forms on the tether. This can either be operator-related where following the design of the inner flushing tube system of the LPM implantation device, a certain operator technique can reduce the clotting risk, 23 or case-by-case–related factors where preprocedural blood transfusion may increase blood viscosity, hence increasing clot formation.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have demonstrated the difficulties encountered during leadless pacemaker implantation when pulling the tether. 6 7 Cipolletta et al 6 reported a clot on a tether. They implanted a leadless pacemaker in a 77-year-old man and experienced difficulty releasing the device and retracting the delivery due to a clot on the tether.…”
Section: Discussionmentioning
confidence: 99%